An evaluation of the operational risk management strategies employed by microinsurance companies in Zimbabwe: case of Econet life (Pvt) Ltd - Muzavazi, Christopher (Midlands State University, 2020)
The management of operational risk has become prominent following the large operational losses experienced by financial institutions in the past years. The research zeroed in on the operational risk management practices in microinsurance companies in Zimbabwe. The main objective of the research was to assess operational risk management strategies employed by the microinsurance companies and how the strategies can be effectively managed to curb the potential losses from occurring. The research revealed the plausible source of operational risks, the strategies adopted by the companies to manage them and the benefits inherent in and effective operational risk management looking at the case of Econet Life Pvt Ltd. The primary data was collected by means of questionnaires and interviews. The data was then analyzed and presented using tables, graphs and charts, visa-vie secondary data. The study showed that more emphasis was being placed on investigating operational risk management in Banks, Microfinance and Traditional Insurance institutions in the financial sector, and less on assessing operational risk management in microinsurance business. The findings exposed the existence of operational risks in microinsurance firms, largely emanating from people, processes and system failures. In this thesis, recommendations were made to try and mitigate operational risks.